DIURNAL TREND OF PARTICULATE MATTER CONCENTRATION AT INDUSTRIAL AREA USING MULTIVARIATE ANALYSIS - Mansor A.A.; Abdullah S.; Napi N.N.L.M.; Ahmed A.N.; Ismail M. (Universiti Malaysia Terengganu, 2023)
Particulate matter is a dominant air pollutant in Malaysia and it is a major emission that has caused many respiratory problems. In this study, the influence of trace gases and meteorological parameters with particulate matter that has an aerodynamic diameter of less than 10 m (PM10) were investigated. Simple linear regression was used to analyse the strength of trace gases and meteorological parameters with PM10, while the Principal Component Analysis (PCA) was used to determine the sources of air pollution. The average concentration of PM10 for a year (January 2010 to December 2010) in Pasir Gudang was 56.567 g/m3,which exceeded the New Ambient Air Quality Standards and international guidelines. The highest mean daily was recorded at 9 a.m (LT) (63.644 pg/ m3), while the lowest was at 11 p.m. (LT) (31.44 g/m3) (12-60 g/m3). PM10 concentrations are significantly correlated with SO2 (R2=0.0302, p<0.01), CH4 (R2=0.0817, p<0.01), RH (R2= 0.0581, p<0.01), NOx (R2=0.11218, p<0.01) and NO (R2=04.0786, p<0.01). The major sources of PM10 are traffic combustion at 35.505%, followed by meteorological factors at 28.972% and traces gases from industry, such as SO2 and NOx, at 11.009%. 2022 Penerbit UMT. All Rights Reserved.